Rainfall Abnormalities in Orissa (Kalahandi District) 1958-67 - Sahu, Dibakar; Pattanaik, J.K.; Pattanaik, S. (Journal of Soil and Water Conservation, 2022)
Orissa is an Agricultural state. Its economy depends upon success of crop production both Kharif and Rabi. Failure of crops due to abnormalities of rainfall throughout the year are frequent now-a-days. Analytical study of rainfall for last 10 years in Orissa from 1958 to 1967 is presented in this article. A bumper harvest in Orissa wholly depends on a good and timely monsoon. Total annual rainfall and its distribution in space and time of the season are responsible for a success. This means the intensity of rainfall and its variability both in Kharif and Rabi seasons are guiding factors for the crop. Conditions forming a flood spell due to heavy intensities of storms and precipitations in last 10 years of Orissa have also been studied and pointed out in case of every district. Simultaneously, a drought spell caused due to low precipitation in Kharif and Rabi in different districts are also pointed out.